Penerapan Protokol Kesehatan pada Masa “New Normal” di Terminal Tipe A Simbuang Kabupaten Mamuju - Agus Erwin Ashari; Haeranah Ahmad; Fahrul Islam (Jurnal Kesehatan Manarang, 2022)
According to data from the COVID-19 Acceleration Task Force on June 13, 2020, there was an increase in positive cases of COVID-19 by 1,014 people, which led to a total of 37,420 cases. Bus stations as a land transportation entrance route, is something that allows it to be the entrance of the corona virus from various regions, especially during the "New Normal" period. The purpose of this study is to find out an overview of the application of health protocols to mada "New Normal" at Simbuang Type A Station in Mamuju Regency. This study is an observational study with a descriptive approach. The research was measured through observations in the field using questionnaires and validated with a checklist based on the Circular letter of the Ministry of Transportation No. SE 11 of 2020 concerning guidelines and technical instructions for the implementation of land transportation during the adaptation period of new habits to prevent the spread of Corona Virus Disease 2019 (Covid-19). Results: research shows that health protocols during the "New Normal" period that qualify at Simbuang Type A Station Mamuju Regency are: availability of hand washing facilities, spraying buses with disinfectants, appeals for the use of masks, and measurement of passengers' body temperature, while those who do not qualify are: : bus passenger capacity, application of physical distancing in the bus and ownership of a passenger's health certificate. Mamuju Regency Simbuang Type A Station has not implemented health protocols properly.